Internalisasi Panca Sradha Dalam Kaderisasi Pejabat Perbendaharaan Pada Kantor Kementerian Agama Kabupaten Buleleng - I Gede Bagus Oka Arda Iswara; Ida Bagus Wika Krishna; I Wayan Gata (Jayapangus Press, 2026)
The cadre formation of treasury officials in religious institutions requires technical competence and moral character because financial management concerns accountability, accuracy, and institutional trust. This study aims to analyze the internalization of Panca Sradha values in the cadre formation of treasury officials at the Office of the Ministry of Religious Affairs of Buleleng Regency. The study employed a qualitative descriptive-interpretative approach. Data were collected through interviews, observation, and documentation involving leaders, administrative managers, treasury officials, finance staff, prospective cadres, and Hindu personnel. Data were analyzed through reduction, classification, interpretation, verification, and triangulation using character education, value internalization, and stewardship perspectives. The findings show that Panca Sradha provides a moral-spiritual foundation for developing integrity, accuracy, self-control, responsibility, honesty, and trustworthiness. Internalization occurs through value communication, dialogue, exemplary conduct, mentoring, gradual assignments, document correction, supervision, evaluation, and work habituation. These processes strengthen procedural compliance, administrative prudence, transparency, timely reporting, courage to reject noncompliant documents, and willingness to correct errors. Karmaphala reinforces awareness of the consequences of actions, while belief in atman and moksa encourages self-control and a service orientation beyond personal interests. The findings reveal that cadre formation lacks a written system and remains dependent on senior officials’ experience, creating risks for competency continuity during personnel changes. The study concludes that Panca Sradha does not replace regulations or technical competence but complements them with a Hindu culturally grounded ethical foundation. Value integration, structured mentoring, written cadre standards, and continuous evaluation are required to prepare competent, accountable, and trustworthy stewards of public finance.